2012
DOI: 10.1177/1039856212470504
|View full text |Cite
|
Sign up to set email alerts
|

Revocation of Community Treatment Orders in a mental health service network

Abstract: The study identified opportunities for improving policy and practice, particularly in relation to reducing the amount of coercion experienced by people on CTOs and improving flexibility of service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Some studies with partial relevance consider supporters' views on restrictive practices from the Australian disability sector 16 and in relation to the use and revocation of community treatment orders. 17,18 As part of a larger study conducted by the Melbourne Social Equity Institute, The University of Melbourne, and funded by the National Mental Health Commission, five focus groups for consumers and five focus groups for supporters were conducted in four capital cities and one regional centre. This article analyses the perspectives of focus group participants related to barriers to reducing seclusion and restraint and the strategies for reducing these practices.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies with partial relevance consider supporters' views on restrictive practices from the Australian disability sector 16 and in relation to the use and revocation of community treatment orders. 17,18 As part of a larger study conducted by the Melbourne Social Equity Institute, The University of Melbourne, and funded by the National Mental Health Commission, five focus groups for consumers and five focus groups for supporters were conducted in four capital cities and one regional centre. This article analyses the perspectives of focus group participants related to barriers to reducing seclusion and restraint and the strategies for reducing these practices.…”
Section: Introductionmentioning
confidence: 99%
“…Of those that did, findings indicated consumers on CTOs had little knowledge about their care plan and what was in it with care plans often out of date and focussed on medication [25, 40, 41]. As the care plan is the means for recording the collaborative care planning process, Owens and Brophy [40] suggested that out dated care plans indicated that such conversations between clinicians and consumers may not be occurring regularly.…”
Section: Core Components Of Case Managementmentioning
confidence: 99%
“…Case managers can have a significant impact on consumers, who can experience the support as either positive or negative with the potential to ‘either assist or obstruct recovery’ [45, 55]. Owens and Brophy [40] for example, found workers were not making sufficient efforts to manage the risk of recall to hospital or the distress experienced by consumers subsequent to this. Establishing good therapeutic relationships and family involvement are necessary to good care coordination [24].…”
Section: Core Components Of Case Managementmentioning
confidence: 99%
See 2 more Smart Citations